1998
DOI: 10.1021/jo971849+
|View full text |Cite
|
Sign up to set email alerts
|

A New Palladium-Catalyzed Intramolecular Allylation to Pyrrolidin-2-ones1

Abstract: A novel palladium(0)-catalyzed cyclization to 3,4-disubstituted pyrrolidin-2-ones has been developed. The new approach relies upon the concomitant generation of stabilized acetamide enolate anions and of a pi-allyl-palladium appendage, properly tethered by a nitrogen atom. Reaction conditions have been optimized for the methoxycarbonyl-stabilized model reaction [(Z)-2 --> 3] and then applied to other substrates. A broad range of acetamide anion stabilizers was shown to allow the desired intramolecular C-C bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…[5] Following the failure of conventional ketene acetal forming conditions with lithium diisopropylamide and chlorosilanes, attention was turned to milder methods based on N,O-bis(trimethylsilyl)acetamide (BSA) and potassium acetate, which we anticipated might provide an effective silylating reagent combination given the acidity of the methylene protons in 1. [6,7] In the initial phase of the work, solutions of 1 and BSA [8] (1.0 equiv) in toluene together with potassium acetate (0.1 equiv) [9] were heated at reflux for 15 h. Homoallylic sulfones 2 were obtained cleanly and in good to excellent yields upon simple reduced-pressure concentration of the reaction mixtures followed by column chromatography on silica gel. We subsequently found that the same transformations could be carried out on 1 by brief exposure to microwave irradiation in the presence or absence of solvent, and that these modified procedures gave similar yields of 2 in most cases where comparison was made.…”
mentioning
confidence: 99%
“…[5] Following the failure of conventional ketene acetal forming conditions with lithium diisopropylamide and chlorosilanes, attention was turned to milder methods based on N,O-bis(trimethylsilyl)acetamide (BSA) and potassium acetate, which we anticipated might provide an effective silylating reagent combination given the acidity of the methylene protons in 1. [6,7] In the initial phase of the work, solutions of 1 and BSA [8] (1.0 equiv) in toluene together with potassium acetate (0.1 equiv) [9] were heated at reflux for 15 h. Homoallylic sulfones 2 were obtained cleanly and in good to excellent yields upon simple reduced-pressure concentration of the reaction mixtures followed by column chromatography on silica gel. We subsequently found that the same transformations could be carried out on 1 by brief exposure to microwave irradiation in the presence or absence of solvent, and that these modified procedures gave similar yields of 2 in most cases where comparison was made.…”
mentioning
confidence: 99%
“…The 1 H, 1 H NOESY spectrum of 8 shows a strong NOE interaction between the two nonequivalent anti protons at the "a" and "c" positions in keeping with this syn geometry. Figure 5 shows a section of the spectrum of 8 recorded at 273 K. We note that in the major conformer A the benzylic protons e show NOE interactions with the methylene protons g, whereas in the minor isomer B these are absent.…”
Section: Entry 8)mentioning
confidence: 69%
“…However, inspection of the 1 H NMR spectra in the region of the central allyl proton resonances reveals that for all of the salts there are 2-3 additional minor syn and anti isomers. [33] The 1 H, 1 H NOESY spectra of 9 a-e at ambient temperature show that all the isomers and specifically the syn and anti isomers are in mutual exchange (Figure 10).…”
Section: Entry 8)mentioning
confidence: 97%
“…A 3,4-trans stereochemistry was assigned to compound 10 on the basis of our previous results [1] and of the expected base-promoted equilibration after CϪC bond formation. On the other hand, the same argument could not be applied to the cyclisation of amide 4.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Such a cyclisation process was based on the interaction between a resonance-stabilized carbanion and an allylic acetate function, tethered through a nitrogen atom (Scheme 1). Careful analysis of the reaction products in all the cases studied revealed that the reaction is completely regio-and stereoselective.…”
Section: Introductionmentioning
confidence: 99%